dBASE IV - Borland International (Scotts Valley, CA : Borland, 1992)
A database management system with menu-driven query and reporting capabilities, automated development features, a powerful application development language and multi-user capabilites for local area networks.
Title from disk label.
System requirements: IBM PC, XT, AT, PS/2 or 100% compatible; 640K RAM; MS-DOS 2.1 or higher or DR-DOS 5.0; hard disk with 4MB free space.
Keywords: Database management -- Software